2021
DOI: 10.3390/ph14090844
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Multimorbidity, Polypharmacy, and Potentially Inappropriate Medication Use in the Older Outpatients: Findings from EuroAgeism H2020 ESR7 Project in Ethiopia

Abstract: Few studies have been conducted on multimorbidity (two or more chronic diseases) and rational geriatric prescribing in Africa. This study examined the prevalence and determinants of multimorbidity, polypharmacy (five or more long-term medications), and potentially inappropriate medication (PIM) use according to the 2019 Beers criteria among the older adults attending chronic care clinics from a single institution in Ethiopia. A hospital-based cross-sectional study was conducted among 320 randomly selected olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
1
19
1
1
Order By: Relevance
“… 30 Our study revealed that 90.1% of patients had potential mild to major DDIs, which lies in the recent systematic review finding (DDIs: 80.5–90.5%). 31 However, it is higher than Bhagavathula et al (2.8%) 22 and Assefa et al (84.3%) studies. Of all the DDIs, enalapril and spironolactone interactions (73%) were the most frequent DDI like de Oliveira et al study result.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“… 30 Our study revealed that 90.1% of patients had potential mild to major DDIs, which lies in the recent systematic review finding (DDIs: 80.5–90.5%). 31 However, it is higher than Bhagavathula et al (2.8%) 22 and Assefa et al (84.3%) studies. Of all the DDIs, enalapril and spironolactone interactions (73%) were the most frequent DDI like de Oliveira et al study result.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings showed that 28.1% of the patients received at least one PIM according to the AGS Beers Criteria. Ethiopian studies conducted in geriatric patients at Tirunesh Beijing Hospital, University of Gondar Teaching Hospital chronic care clinic, and Jimma Medical Center reported that 46.9%, 21 47.2%, 22 and 83.1% 23 of older adults were prescribed at least one PIM, respectively. In these studies, medication appropriateness was assessed using Beers criteria in two studies, 22 , 23 while the remaining study 21 used both WHO core prescribing indicators and Beers criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, major polypharmacy (3%) was lower, whereas total polypharmacy (71%) was higher than in similar studies in other settings. Polypharmacy (the use of five or more drugs) was found to be 24.1% in an older patient polypharmacy study in western Ethiopia [ 31 ]. A recent meta-analysis of the elderly Ethiopian population found 33% polypharmacy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why antibiotics use was high at the Edna Adan University was unclear and beyond the scope of this study. Studies in selected public hospitals in eastern Ethiopia also revealed that antibiotic use was more widespread [ 31 ]. This suggests that the abuse and indiscriminate use of antibiotics is a common trend and the regulatory system is loose in the East Africa.…”
Section: Discussionmentioning
confidence: 99%